The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.17344/acsi.2020.5963
|View full text |Cite
|
Sign up to set email alerts
|

GO/PAMAM as a High Capacity Adsorbent for Removal of Alizarin Red S: Selective Separation of Dyes

Abstract: Adsorption of Alizarin Red S (ARS) on graphene oxide/poly(amidoamine) (GO/PAMAM) was studied at different ARS initial concentrations, temperatures, pHs, shaking rates and contact times. Adsorption sites of GO/PAMAM were phenolic –OH (Ph) group of GO and amine groups (–NH2, –NH+ 3 and –NHR+2) of PAMAM dendrimer moieties of GO/PAMAM. At pH = 2 and 318 K, maximum adsorption capacity (qe,max) of the adsorbent was 1275.2 mg g–1 which is one of the highest capacity in the literature. Thus, GO/PAMAM in this work acte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 45 publications
0
3
0
Order By: Relevance
“…On the other hand, new peaks emerged at 1532 cm −1 , which is characteristic for N-H vibration of amide groups, at 1246 and 1028 cm −1 , which are attributed to C-N bonds and another vibration band at 1628 cm −1 assigned to amide C=O stretching vibration mode [40]. The new bands confirm the incorporation of PAMAM into the rGO aerogels by cross-linking between the carboxylic groups in GO and amine groups in PAMAM dendrimers [37,38,[41][42][43]. By comparing the effect of dendrimer generation (primary amine group number) and T HT , it can be observed that above mentioned spectra modifications occur already at lower T HT in the case of PAMAM G3, while G7 results in weaker modification of the bands.…”
Section: Resultsmentioning
confidence: 78%
See 1 more Smart Citation
“…On the other hand, new peaks emerged at 1532 cm −1 , which is characteristic for N-H vibration of amide groups, at 1246 and 1028 cm −1 , which are attributed to C-N bonds and another vibration band at 1628 cm −1 assigned to amide C=O stretching vibration mode [40]. The new bands confirm the incorporation of PAMAM into the rGO aerogels by cross-linking between the carboxylic groups in GO and amine groups in PAMAM dendrimers [37,38,[41][42][43]. By comparing the effect of dendrimer generation (primary amine group number) and T HT , it can be observed that above mentioned spectra modifications occur already at lower T HT in the case of PAMAM G3, while G7 results in weaker modification of the bands.…”
Section: Resultsmentioning
confidence: 78%
“…For a given concentration of dendrimer, thinner (more transparent) rGO sheets were observed in the resulting aerogels by modification with higher generation (G7) that is attributed to dendrimer size characteristics. It was reported that the cross-linking between the PAMAM dendrimers and rGO sheets proceeds between the amine groups at the surface of dendrimer and carboxylic groups in rGO [38]. Thus, in the case of G3, a planar molecule, the interaction would proceed horizontally from plane to plane.…”
Section: Resultsmentioning
confidence: 99%
“…Upon the addition of the dendrimer for the synthesis of the modified aerogels, new peaks related to amides and corresponding to the coupling of the C–N stretching vibration emerged at 1549, 1452, 1347, 1225, and 1086 cm −1 , together with another vibration band at 1630 cm −1 attributed to the amide C=O stretching vibration mode corresponding to NH 2 deformation [ 20 , 26 , 27 , 28 ]. The appearance of the new bands confirmed the incorporation of PAMAM into the modified GO aerogels by cross-linking between the carboxylic groups in GO and amine groups in PAMAM dendrimers [ 20 , 29 , 30 , 31 ]. The spectral features of the aerogel modified with the increased addition of the dendrimer confirmed these findings, as the above-mentioned band modifications were more evident (i.e., more intense peaks emerged, while some peaks of GO (the band at 1714 cm −1 ) completely disappeared).…”
Section: Resultsmentioning
confidence: 84%